Short Wavelength (Blue) Light Is Protective for Lens-Induced Myopia in Guinea Pigs Potentially Through a Retinoic Acid–Related Mechanism - Yu, Manrong (Invest Ophthalmol Vis Sci, 2021)
PURPOSE: To investigate the effect of short-wavelength light (SL) on guinea pigs with lens-induced myopia (LIM) and the possible retinoic acid (RA)–related mechanisms. METHODS: Two-week-old guinea pigs (n = 60) with monocular −5D lenses were reared under white light (WL, 580 lux) or SL (440 nm, 500 lux). The left eyes were uncovered as control. Refractive error (RE) and axial length (AL) were measured at baseline, one week, two weeks, and four weeks after intervention. Retinal RA was measured from four guinea pigs after two and four weeks of treatment with HPLC. Two-week-old guinea pigs (n = 52) with monocular −5D lens were fed with either RA or its synthesis inhibitor citral every third day in the morning, and half from each group were reared under WL or SL conditions. RE and AL were recorded at baseline and two and four weeks after intervention. Retinal RA was measured after four weeks of intervention. RESULTS: At the end of treatment, guinea pigs exposed to SL were less myopic than to WL (2.06 ± 1.69D vs. −1.00 ± 1.88D), accompanied with shorter AL (P = 0.01) and less retinal RA (P = 0.02). SL reduced retinal RA even after exogenous RA supplementation (P = 0.02) and decelerated LIM compared to WL (1.66 ± 1.03D vs. −3.53 ± 0.90D). Citral slowed ocular growth, leading to similar RE in W+CI and S+CI groups (3.39 ± 1.65D vs. 5.25 ± 0.80D). CONCLUSIONS: Overall, SL reduced LIM in guinea pigs, even in those supplemented with oral RA, accompanied by reduced retinal RA levels. Oral RA accelerated eye elongation, but citral equally decelerated eye elongation under SL and WL with no significant retinal RA reduction.